Accelerating maturation of Chinese rice wine by using a 20 L scale multi-sweeping-frequency mode ultrasonic reactor and its mechanism exploration - Zhuofan He; Furong Hou; Yansheng Du; Chunhua Dai; Ronghai He; Haile Ma (Ultrasonics Sonochemistry)
The formation of flavor in traditional Chinese rice wine requires a long aging process. To accelerate the maturation of rice wine, a 20 L scale multi-sweeping- frequency mode ultrasonic reactor was employed in this study to explore the promoting effects. Rice wines were subjected under 10 combined types of sonication treatments with 20/28/40 kHz in single/double/triple frequencies, and in fixed or sweeping modes, respectively. Then samples were aged in room temperature for up to 180 days. A 7.3 % increase of total esters content was observed in rice wine sample after treated by a fixed 40 kHz ultrasonication with 50 W/L intensity at 30 °C for 15 min, compared with the untreated sample. After sonication and stored for six months, 286.78 % increase of the volatile esters was found, compared to rice wine without ultrasoinc treatment and stored at same condition for same time. And the total volatile alcohol substances and total volatile aldehydes in rice wine decreased by 12.95 % and 67.46 %, while the total volatile acids increased by 17.11 %, respectively. The research results also demonstrated that ultrasonic induced free radicals accounted for the variations of rice wine properties. And the correlation between the acoustic cavitation and the flavor formation was also observed.